2011
DOI: 10.1007/s13595-011-0135-6
|View full text |Cite
|
Sign up to set email alerts
|

Walnut (Juglans spp.) ecophysiology in response to environmental stresses and potential acclimation to climate change

Abstract: Context Walnuts (Juglans spp.) are ecologically and commercially important trees, yet synthesis of past and current research findings on walnut ecophysiology is lacking, especially in terms of potential acclimation to climate change.• Aims This study aims to (1) investigate walnut ecophysiology by comparing its attributes to associated deciduous angiosperms, (2) address potential acclimation of walnut to climate change, and (3) identify areas for prioritization in future research.• Results There is considerabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 108 publications
(138 reference statements)
0
24
0
Order By: Relevance
“…We also found that the locus AX-170770379, strongly associated with harvesting date (Marrano et al 2019), falls within a genomic region on Chr1 with an FST value equal to 0.39 and lower genetic diversity in the western genotypes (ROD = 0.63; Supplemental Table S19 ). Looking at the phenotypic effect of this SNP on the harvest date of the 23 founders, we observed that most of the western genotypes are later harvesting than the eastern ( Supplemental Figure S13 ), suggesting differences in the timing of phenological events between these two groups as adaptation to the different climate conditions present in their countries of origin (Gauthier and Jacobs 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We also found that the locus AX-170770379, strongly associated with harvesting date (Marrano et al 2019), falls within a genomic region on Chr1 with an FST value equal to 0.39 and lower genetic diversity in the western genotypes (ROD = 0.63; Supplemental Table S19 ). Looking at the phenotypic effect of this SNP on the harvest date of the 23 founders, we observed that most of the western genotypes are later harvesting than the eastern ( Supplemental Figure S13 ), suggesting differences in the timing of phenological events between these two groups as adaptation to the different climate conditions present in their countries of origin (Gauthier and Jacobs 2011).…”
Section: Resultsmentioning
confidence: 99%
“…The event caused obvious changes to the climatic suitability of the studied co-occurring species, irrespective of species' fit to previous climatic conditions. The fact that species historically living under more suitable climatic conditions failed to show greater resistance to an extreme drought event could be explained by the fact that species chronically subjected to suboptimal conditions can become acclimated (Gauthier and Jacobs 2011). Several studies have reported that trees that have previously experienced favorable conditions (i.e., that promoted growth) showed higher vulnerability to drought (McCulloh et al 2012, Rowland et al 2014.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, total annual precipitation amounts were higher at areas in proximity to these mountain chains as recorded by the German Meteorological Service. 31 Given the correlation of altitude with 2 H-values (‰) of precipitation, 2 H-values (‰) of the walnuts were investigated for the same correlation. With the walnut sampling site in BW being at greater altitude than the one in HE (270 m a.s.l.…”
Section: H Values (‰) Of Walnuts From Different Regions In Germany Inmentioning
confidence: 99%
“…Walnut trees and other tree crops are characterized by limited nitrogen-uptake, which usually lies at ∼30-50% of available nitrogen. 2,40,45 For instance, field studies with 14 N-labeled fertilizers in matured walnut trees of the cultivar Juglans regia cv. Hartley resulted in a rather poor nitrogen-fertilizer use efficiency of 29%, and only ∼8% of totally applied nitrogen-fertilizer was used by the trees for fruit and leaf formation in the year of fertilization.…”
Section: N-values (‰) Of German Walnutsmentioning
confidence: 99%
See 1 more Smart Citation